A recontextualização do discurso pedagógico da alfabetização construtivista por alfabetizadoras formadas na FaE/UFPel - Porto, Gilceane Caetano (2011)
This research aimed to understand how thw primary teachers which realize the Pedagogy Course in FaE/UFPEL in the period of the 1986 to 2005 recontextualize the primary teaching constructivist pedagogical speech.The research has the qualitative caracter, was carried out with five primary teachers which ones work in the county teaching public net in Pelotas more than three years. One of them granted only one interview because she is not longer acting in the alfabetization class. The other four teachers which made part of teh investigation granted two interviews and had your practices followed in the year of 2010 and provided their plan class diaries for analysis. From the construciuvist alfabetization theory, of the pedagogical texts produced by the trainers and of the alfabetization pedagogical practices, three fields of the alfabetization constructivist pedagogical speech was made up. The fisrt one was named as a primary field of the production of alfabetization constructivist pedagogical speech. For that, the psychogenesis production field was featured, establishing some parameters needed to evaluate the recontextualization process where the constructivist alfabetization speech is delocated from one field to other. Five indicators were building which characterize a pedagogical constructivist alfabetization practice , these indicators formed the basis to the analysis. The second field was constituted on the Thesis was the secundary field of reproduction of the constructivist alfabetization speech, composed fundamentally by the agents and agencies of graduation formation of the research subjects. For the constitution of this field were analyzed the curriculum, teaching plans, disciplin programs which made part of the analyzed period curriculum, specially the references. The third field was constituted in this Thesis was that related to the pedagogical practices of teh primary teachers. The analysis of the recontextualiztion was made troughout the recontextualization rules. The practices were analyzed from teh classification concepts and the pedagogical speech framework. From the analyzed data is possible to recognize, as was showed by Bernstein (1996), that the speech when pass from a field to another it is descontextualized e recontetualized by the differnt influences and disputes which are established in the new context. It is concluded that the secunadary recontextualization produced in the Education College of the UFPEL constituted as an element of efective production of a new text, generator of new alfabetization practices. This speech when is recontextualized configures itself as a new text and creates a speech which for a side presents characteristics related to the constructivist alafabetization theory, by other hand is a product of this recontextualization process. The research found different pedagogical alfabetization speechs, by one side the primary teachears analyzed do not follow a alfabetization method, as the teachers did some decades ago. In other hand, the teachers also did not follow a constructivis alfabetization padagogy, paradigm which agree with their formation tima. The pedagogical inheritance configures itself as being very strong, despite the formation in the graduation level. So any alfabetization practice observed follow an analytic alfabetization method or synthetic, but all cultivate in their practices activities that ones with directly relates to this methods considered traditional in the alfabetization history.